2024
DOI: 10.1007/s12519-024-00805-2
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical-based phenotypes in children with pediatric post-COVID-19 condition

Lieke C. E. Noij,
Jelle M. Blankestijn,
Coen R. Lap
et al.

Abstract: Background Pediatric post coronavirus disease 2019 (COVID-19) condition (PPCC) is a heterogeneous syndrome, which can significantly affect the daily lives of children. This study aimed to identify clinically meaningful phenotypes in children with PPCC, to better characterize and treat this condition. Methods Participants were children with physician-diagnosed PPCC, referred to the academic hospital Amsterdam UMC in the Netherlands between November 2021 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Subsequent to the prevalence of the Alpha and Delta variants during the initial pandemic waves in the pre-Omicron period, SARS-CoV-2 Omicron (PANGO B.1.1.529) swiftly propagated across Europe from December 2021 to February 2022. Clinically, Omicron variant induced less severe acute illness than its predecessors, and certain studies reported a reduced incidence of post-acute phase impacts [13][14][15][16][17][18][19], both in adults and children [20][21][22][23][24]. Nevertheless, conflicting data have surfaced in the literature [25], and the potential influence of prior vaccination remains uncertain [26][27][28].Valuating the genuine repercussions of SARS-CoV-2 infection in the realm of LONG COVID following the acute phase proves intricate due to myriad factors.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to the prevalence of the Alpha and Delta variants during the initial pandemic waves in the pre-Omicron period, SARS-CoV-2 Omicron (PANGO B.1.1.529) swiftly propagated across Europe from December 2021 to February 2022. Clinically, Omicron variant induced less severe acute illness than its predecessors, and certain studies reported a reduced incidence of post-acute phase impacts [13][14][15][16][17][18][19], both in adults and children [20][21][22][23][24]. Nevertheless, conflicting data have surfaced in the literature [25], and the potential influence of prior vaccination remains uncertain [26][27][28].Valuating the genuine repercussions of SARS-CoV-2 infection in the realm of LONG COVID following the acute phase proves intricate due to myriad factors.…”
Section: Introductionmentioning
confidence: 99%